2015
DOI: 10.1155/2015/910168
|View full text |Cite
|
Sign up to set email alerts
|

Core Muscle Activity during TRX Suspension Exercises with and without Kinesiology Taping in Adults with Chronic Low Back Pain: Implications for Rehabilitation

Abstract: This study aimed to examine the effects of kinesiology taping (KT) and different TRX suspension workouts on the amplitude of electromyographic (EMG) activity in the core muscles among people with chronic low back pain (LBP). Each participant (total n = 21) was exposed to two KT conditions: no taping and taping, while performing four TRX suspension exercises: (1) hamstring curl, (2) hip abduction in plank, (3) chest press, and (4) 45-degree row. Right transversus abdominis/internal oblique (TrAIO), rectus abdom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 26 publications
1
17
0
1
Order By: Relevance
“…After removing irrelevant studies and duplicates, 19 articles that met our inclusion criteria were carefully identified. Articles which did not use pain or disability as outcome measure 1012 or were not randomized controlled trials 13–16 were removed. Follow-up study 17 (further study of Parreira in 2014) or study with non-comparable baseline parameters were excluded.…”
Section: Resultsmentioning
confidence: 99%
“…After removing irrelevant studies and duplicates, 19 articles that met our inclusion criteria were carefully identified. Articles which did not use pain or disability as outcome measure 1012 or were not randomized controlled trials 13–16 were removed. Follow-up study 17 (further study of Parreira in 2014) or study with non-comparable baseline parameters were excluded.…”
Section: Resultsmentioning
confidence: 99%
“…Altering the sling points and heights of the dangling rope in sling-based training helps patients train specific muscle groups and provides an unstable surface where muscle groups receive antigravity training. In sling-based training, a sling supports the weight of various body parts; therefore, compared with traditional training, it is an easier program for patients to improve body trunk muscle strength [ 25 ]. Sling-based training was often practiced to train core muscle groups, such as the chest, waist, and abdomen, and to improve muscle strength and stability of the body trunk [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In sling-based training, a sling supports the weight of various body parts; therefore, compared with traditional training, it is an easier program for patients to improve body trunk muscle strength [ 25 ]. Sling-based training was often practiced to train core muscle groups, such as the chest, waist, and abdomen, and to improve muscle strength and stability of the body trunk [ 25 , 26 ]. To the best of our knowledge, this is the first study to investigate the application of sling-based training to PFPS-affected lower extremities.…”
Section: Discussionmentioning
confidence: 99%
“…The suspension-training program was composed of diverse TRX® suspension trainer exercises (TRX® suspension trainer, 755 Sansome Street, San Francisco, CA, USA). The suspension-training program (Table 1) was applied during 5 weeks, three times per week, before to each training session, with an emphasis on movement quality (i.e., technique), replacing a part of the athlete´s normal judo training routine, following previous recommendations (Bettendorf, 2010;Byrne et al, 2014;Fong et al, 2015;Imai, Kaneoka, Okubo, Shiina, Tatsumura, Izumi, & Shiraki, 2010;Mok et al, 2015;Myer, Ford, Brent, & Hewett, 2006).…”
Section: Training Programmentioning
confidence: 99%
“…Training programs on unstable surfaces may aid to develop more than one physical performance trait relevant for judo, with meaningful effects in a relatively short period. For example, among unstable training devices, suspension training offer the highest activation of core stabilizing muscles (Byrne, Bishop, Caines, Crane, Feaver, & Pearcey, 2014;Fong, Tam, Macfarlane, Ng, Bae, Chan, & Guo, 2015;Mok, Yeung, Cho, Hui, Liu, & Pang, 2015), key to judo athletes. In addition, motor control, endurance, strength and muscle power (Bettendorf, 2010) may be significantly improved through suspension training, physical performance traits that may aid judo athletes to perform better and reduce their risk to sustain injuries.…”
Section: Introductionmentioning
confidence: 99%